Brent and Urals Oil Price Control Mechanisms - Solovieva, Yuliana Vladimirovna; Chernyaev, Maxim Vasilyevich; Nezhnikova, Ekaterina Vladimirovna (International Journal of Energy Economics and Policy, 2021)
The article considers the main mechanisms for controlling the formation of oil prices, including Brent and Urals brands. Based on the analysis of trends in the oil market and their dynamics over the past decades, the authors identify factors affecting pricing in the oil market, different oil market price control systems, and their dynamics. Our results show that there is a substantial price gap in the world oil market between the Brent reference grade and the Urals crude grade, while the formation of the Urals brand price is opaque. Comparing the key characteristics of different systems of price control in the oil market, we revealed that under the influence of external and internal factors, the system of control over pricing in the oil market underwent significant changes throughout its existence. The authors conclude that at present, there are real prerequisites for the institutional correction of the global oil market in terms of strengthening the administrative levers of developed countries control over exchange and OTC pricing mechanisms. Keywords: oil market, Brent brand, Urals brand, oil price, pricing factors, pricing system, pricing control mechanism. JEL Classifications: G23; L52; O24 DOI: https://doi.org/10.32479/ijeep.11022